Financing Services of General Economic Interest
XVIII, 298 p.
Keywords: This book examines the legacy of the 2003 ruling of the Court of Justice of the European Union in Altmark. This case changed the direction of how Services of General Economic Interest (SGEI) should be funded in the EU against a background of liberalisation, and the need for efficiency and global competitiveness. The book examines the European Commission’s response to the Altmark ruling in the measures known as the ‘Altmark-Monti-Kroes Package’ and charts the review of this package from 2009 culminating in a new package of measures, known as the ‘Almunia Package’. The seemingly technocratic idea of a review of the ‘Altmark-Monti-Kroes Package’ could not have anticipated the demanding and changed economic and constitutional context of the EU in 2009. It is in this light that the authors in this book explore in great detail the different components of the new ‘Almunia Package’ of measures introduced in 2011-2012, offering a critical review and highlighting where the future direction of the regulation of SGEI may lead as the EU struggles in an economic climate of austerity to balance a new constitutional dimension of a ‘highly competitive social market economy’ with a modernisation agenda for the single market. This book is a valuable source of information for politicians, lawyers and economists involved in practice and policy-making in the field of the provision of public services.